Process network modularity, commonality, and greenhouse gas emissions. Issue 2 (18th March 2019) - Dooley, Kevin J.; Pathak, Surya D.; Kull, Thomas J.; Wu, Zhaohui; Johnson, Jon; Rabinovich, Elliot
Abstract: A process network is a complex system of linked unit processes that constitute the life cycle of a product. In this article, we consider how the structural and functional characteristics of a product's process network impact the network's collective greenhouse gas (GHG) emissions. At a unit process level, GHG emissions are primarily related to process efficiency. We hypothesize that a process network's GHG emissions will be less when the process network has a modular structure and when its constituent unit processes are more functionally similar. A modular process network architecture promotes autonomous innovation and improvements in knowledge management and problem‐solving capabilities, leading to more efficient processes. Functional commonality in a process network enables economies of scale and knowledge spillover and also leads to process efficiencies, thus reducing GHG emissions. We test these two hypotheses using a sample of 4, 189 process networks extracted from an environmental life cycle inventory database. Empirical results support our hypotheses, and we discuss the implications of our findings for product development and supply network design. Abstract : Author Video